answersLogoWhite

0


Best Answer

8x - 6y = 18

4x - 6y = 6

from the first equation:

6y = 8x - 18

substitute this value in the second equation:

4x - (8x - 18) = 6

4x - 8x + 18 = 6

-4x = 6 - 18

-4x = -12

x = 3

Solve for y :

8 x 3 - 6y = 18

24 - 6y = 18

6y = 6

y = 1

User Avatar

Wiki User

โˆ™ 2010-06-03 18:17:35
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1216 Reviews

Add your answer:

Earn +20 pts
Q: 8x-6y equals 18 and 4x-6y equals 6?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked